2020
DOI: 10.1556/004.2020.00006
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and biochemical reference intervals in healthy racing and retired Italian Greyhounds

Abstract: In view of the enormous variability of dog breeds, breed-specific reference intervals (RIs) are recommended for use in veterinary clinical decision-making. The aim of this study was to determine whether RIs of the general canine population may be applied to the Italian Greyhound (Piccoli Levrieri Italiani or PLI), and to generate breed-specific RIs, where appropriate. Sixty-three privately owned clinically healthy fasted dogs were examined. Routine haematology and biochemistry were performed on 58 enrolled pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Additionally, even though the differences between the breeds with the highest and lowest measurand levels were relatively large across the different measurands, a breed-specific concentration exceeded the reference intervals only in creatinine. GH had remarkably higher creatinine concentration than other breeds, supporting a well-recognized and documented phenomenon [16,6366]. Moreover, in the vast majority of the measurands, GH was systematically different from most other breeds.…”
Section: Discussionsupporting
confidence: 71%
“…Additionally, even though the differences between the breeds with the highest and lowest measurand levels were relatively large across the different measurands, a breed-specific concentration exceeded the reference intervals only in creatinine. GH had remarkably higher creatinine concentration than other breeds, supporting a well-recognized and documented phenomenon [16,6366]. Moreover, in the vast majority of the measurands, GH was systematically different from most other breeds.…”
Section: Discussionsupporting
confidence: 71%
“…RIs are pivotal in the interpretation of clinicopathological data and to assess health status in both human and veterinary medicine. Breed influence has been previously reported in dogs 16,[19][20][21][22] and cats. [13][14][15] Nevertheless, to our knowledge, no studies on haematological and biochemical RIs in healthy Ragdoll cats have been reported.…”
Section: Discussionmentioning
confidence: 82%
“…Differences in the reference intervals between dog breeds have been recognized for many years. For example, serum reference intervals for Italian Greyhounds were wider for total protein and cholesterol and higher for albumin, calcium, and iron than previous intervals for multiple breeds 4 . Breed‐specific differences were also found for adult Dogue de Bordeaux for ALT, AST, total cholesterol, and lipase 5 .…”
Section: Introductionmentioning
confidence: 86%
“…For example, serum reference intervals for Italian Greyhounds were wider for total protein and cholesterol and higher for albumin, calcium, and iron than previous intervals for multiple breeds. 4 Breed-specific differences were also…”
mentioning
confidence: 98%